(untitled) (Research, Society and Development, 2021)
This article studies the impacts of social isolation during the COVID-19 pandemic, on the behavioral and cognitive aspects of children aged 0 to 6 years. To accomplish this evaluation, a questionnaire was made with the parents/guardians of these children. In a second part, a semi-structured interview was made to deepen the knowledge based on the answers and information previously provided. The research aims to confirm or contradict the data raised in the theoretical framework, the content of this article may be of great regard to psychologists, pedagogues, parents, psychiatrists and people in the health area who may be interested in the theme, as there aren’t many articles, research and studies on this subject in Portuguese. The results of this study showed that the vast majority of parents / guardians are extremely overloaded and that many children show changes in both behavior and cognition. Beyond the increased use of screens and decreased of physical activity and body movement in general, there are also the losses and benefits of exclusive contact with family members.